Governança pública e gestão do conhecimento nas escolas do legislativo das câmaras municipais - Perelles, Priscila (2021)
The present study aims to analyze the relationship between maturity in Knowledge Management and training in public governance skills in the Legislative Power through the legislative schools of the municipal councils. Its relevance lies in the proximity of councilors to society, forming an interaction environment that, well guided by principles of public governance disseminated by legislative schools, has the ability to awaken participatory social engagement in the political-decision-making process and qualified social control. The theoretical framework is based on public governance, covering origin, concept and principles, as well as the position of the Legislative Power in this relational dynamic. And, also, in Knowledge Management directed to the public sector. The research of an applied nature uses a mixed approach, qualitative and quantitative, and exploratory and descriptive objectives. The method selected is a multiple case study. For data collection, two different techniques were chosen: i) questionnaires addressed to councilors and school managers of the legislature; and ii) observation of electronic portals. The research sample consisted of 77 municipal councils that have legislative schools in their organizational structure and their 1,579 councilors. Valid responses were collected from 28 legislative school managers and 131 parliamentarians. The result of the research revealed that the knowledge of public governance is considered important competences for the exercise of the parliamentary mandate, and the degree of mastery of the associated themes by the parliamentarians is also high. On the other hand, the frequency of training actions, in general, does not seem to meet the perceived gaps in certain subjects and, in others, exceeds the perceived need. This mismatch is consistent with data that show that Knowledge Management in city councils, as a rule, is in initiation and expansion stages, and in none of the surveyed city councils the degree of full maturity was identified. It is also consistent with the result of observing the communication of the principles of transparency, participation and accountability of schools in the legislature in the electronic portals of municipal councils. The research shows that the transparency indicators had the best results. The data suggest, therefore, that the potential of legislative schools is still little explored in the electronic channels of communication between the Legislative Power and society.